ROLE OF PALATAL RUGAE PATTERNS (RUGOSCOPY) IN FORENSIC FIELD: PERAN POLA RUGAE PALATAL (RUGOSKOPI) DALAM BIDANG FORENSIK - Subhaini Jakfar (TALENTA, 2011)
The development of forensic identification in dentistry is growing significantly to serve judicial system, there are teeth, lip prints, bite marks, dental arches, dental records, DNA, palatal rugae patterns, etc., which is called forensic odontology. Another forensics identification in dentistry is restoration material used in oral cavity. All of them are used in forensic identification for disaster victim identification, criminal and research. Differences of them are allowing fast and secure identification process, however, in some cases, these techniques can not always be applied which is necessary to apply different and less known techniques. This article reviews some of the useful palatal rugae patterns as forensic identification or rugoscopy by using gypsum dental cast. The palatine rugae is an interested forensic because of its typical pattern of orientation, number, position, and size which can be used to differ ethnicity or sex, and palatine rugae is permanent and unique to each person, so it can be used to assist the forensic odontologist in the identification of a person. In conclusion, palatine rugae is significant use in clinical and forensic purposes.